Common Pitfalls in Mathematical Induction - Ratnah Lestary; Heri Apriyanto (J-PiMat : Jurnal Pendidikan Matematika, 2026)
Many students encounter difficulties when learning the material on mathematical induction. A lack of understanding of the principles of mathematical induction leads students to make errors when attempting to prove mathematical statements repeatedly. To help students avoid these pitfalls, it is essential to analyze common pitfalls that frequently occur in the proof process using mathematical induction. This study employed a qualitative approach, utilizing a case study design, to analyze the answer sheets of 56 students from the first semester of the Mathematics Education program. The answers were categorized into five groups based on the types of difficulties encountered. From each category, one information-rich case was selected for further interviews. The research revealed several common pitfalls in mathematical induction: (1) failure to write the complete mathematical statement to be proven, (2) misunderstanding the importance of defining the domain of numbers, (3) using examples to prove the mathematical statement, (4) pitfall due to lack of metacognitive control, and (5) performing operations on both the left and right sides of the mathematical statement in the second stageKeyword: Error Analysis; Mathematical Proof; Mathematical Induction; Pitfall